Effectiveness Of Activated Carbon From Bamboo Chips For Industrial Wastewater Treatment - Nur Halissa Syuhada, Abdul Razak (2022)
The river system surrounding the Gebeng industrial area has experienced excessive stress as a result of the rapid growth of production in the area, which includes various factories and mining activities. Based on the effluent discharged, industrial activities based on petrochemical and bauxite mining have been listed as contributors to the pollution of chemicals and heavy metals in water bodies. Heavy metals, which have accumulated in the soil for a long time, are harmful to marine ecosystems. Water pollution with organic and inorganic compounds such as metals and pesticides has prompted researchers to improve purification and extraction methods such as adsorption of pollutants using activated carbon. The aim of this study was to see the effectiveness of bamboo chip activated carbon in treating polluted wastewater from Gebeng industrial area. The physical and chemical parameters of the water were analyzed to assess the level of initial contamination, which was then compared with the level of contamination after four weeks of treatment. pH, turbidity, total suspended solids (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), as well as zinc (Zn) and copper (Cu). heavy metals (Cu). In addition, the objective of this project is to identify the level of pollutants contained in the wastewater of Gebeng industrial area and further to determine the ability of activated carbon from bamboo chips in treating wastewater. The final objective is to compare physical performance with 500 ℃ and 400 ℃ activation in wastewater treatment. The process to produce activated carbon is to burn bamboo chips to two temperatures of 500 ℃ and 400 by using a furnace for several hours. After that, the bamboo chips are cooled at room temperature and crushed into powder and divided into three ratios for the two temperatures. After that each ratio of 20, 30 and 40g was mixed with zinc chloride of 10g. Next, it is heated on a heat plate until well blended and rinsed with distilled water and baked in an oven with a temperature between 100 ° C and 110 ° C for 6 hours. Upon completion, the activated carbon was mixed with wastewater and left for one night to dissolve thoroughly and filtered to be tested for each ratio in order to prove the effectiveness of the bamboo chips. Once the data are taken as a whole it can be concluded that at a temperature of 400 ° C and a ratio of 40g is more effective than other temperatures and ratios. But the whole data is taken for all parameters.